Corruption and Good Governance in Asia - Nicholas Tarling (Routledge, 2005)
Governance and corruption in Asia have been the subject of much recent writing, both before and after the crisis of 1997. The conference at the New Zealand Asia Institute, at which most of the chapters in this book were originally given as papers, sought to contribute to the debate in a number of ways. First, it was felt that recent writing, though extensive, had in some ways been too narrow. Much of it was concerned with the misuse of foreign aid or the misapplication of foreign investment, and insofar as it was a question of reform or remedy it tended to focus on an external accountability. That is, of course, to be expected in an age of ‘globalisation’, and it is not irrelevant. But the conference and this book are based on the assumption that corruption takes different forms at different times, and that even a more limited and focused view will benefit from recognising that.